2017
DOI: 10.1111/jicd.12257
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of natural early caries lesions in vitro by P11‐4 monitored with photothermal radiometry and luminescence

Abstract: Aim The efficacy of self‐assembling peptide P11‐4 to regenerate enamel in natural early caries lesions was evaluated over 50 days by photothermal radiometry and luminescence using The Canary System (CS) and The Canary Lab (CL). Methods Baseline readings for sound and carious sites on smooth surfaces of extracted teeth were obtained by scanning with CS and CL. Teeth were then randomly assigned to a treatment group (TG, treated with P11‐4), a placebo group (PG, same vehicle as treatment group without P11‐4), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 25 publications
(55 reference statements)
1
30
1
3
Order By: Relevance
“…This prepositions them for nucleation of hydroxyapatite (Aggeli et al, 2003;Kind et al, 2017;Kirkham et al, 2007). Several approaches, in vitro and in vivo, have recently demonstrated the effectiveness of self-assembling peptide P11-4 in remineralizing early carious lesions as well as in preventing demineralization of enamel (Brunton et al, 2013;Ceci et al, 2016;Jablonski-Momeni and Heinzel-Gutenbrunner, 2014;Silvertown et al, 2017;Soares et al, 2017); however, none have investigated P11-4 on dentin surfaces. Thus, the current analysis was the first to evaluate the use of self-assembling peptide P11-4 as a pretreatment for demineralized dentin and its influence on the microtensile bond strength of two different adhesive systems.…”
Section: Discussionmentioning
confidence: 99%
“…This prepositions them for nucleation of hydroxyapatite (Aggeli et al, 2003;Kind et al, 2017;Kirkham et al, 2007). Several approaches, in vitro and in vivo, have recently demonstrated the effectiveness of self-assembling peptide P11-4 in remineralizing early carious lesions as well as in preventing demineralization of enamel (Brunton et al, 2013;Ceci et al, 2016;Jablonski-Momeni and Heinzel-Gutenbrunner, 2014;Silvertown et al, 2017;Soares et al, 2017); however, none have investigated P11-4 on dentin surfaces. Thus, the current analysis was the first to evaluate the use of self-assembling peptide P11-4 as a pretreatment for demineralized dentin and its influence on the microtensile bond strength of two different adhesive systems.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the effectiveness of self‐assembling peptide P 11 ‐4 has been investigated ex vivo with carious diagnostics, and in a clinical safety trial treating class V carious lesions . The application of P 11 ‐4 on 15 carious lesions led to a significant reduction of the lesion size, and a reversal of the lesion activity toward remineralization within 30 days of the single application, as assessed on randomized clinical photographs by blinded assessors.…”
Section: Introductionmentioning
confidence: 99%
“…For SAP P 11 -4 to be translated into daily clinical practice, it is essential that clinicians can visualize the treatment effect with available diagnostics. Both ex vivo and in vivo studies have reported the successful use of laser fluorescence, PTR-LUM, Impedance, QLF and radiography in monitoring remineralization after SAP P 11 -4 application in a time-dependent manner 12,13,[16][17][18][19][20] .…”
mentioning
confidence: 99%